(untitled) (Research, Society and Development, 2020)
Studies about ventures and work have suggested new evaluating perspectives related to professional development and strategies on people’s management aiming to understand in a more specific way the relation work-job-productivity-health. In this context, we search to comprehend the venture’s role concerning a professional and social protection and safety; thus, this paper aims to verify a theorical model through the organizational support, positive psychological capital and future’s expectancy. 214 workers, men and women, aged from 19 to 61 years old, from public and private companies in João Pessoa-PB city answered to the organizational support perception scale, future expectancy and socio-demographical characterization. It has been observed that the independent model through the organizational support, positive psychological capital and future’s expectancy was not significant, suggesting a mediational model, in which the organizational support perception influences the future’s expectancy, with the psychological capital mediating this relation. In general, the importance of the venture’s emotional investment is highlighted (through the psychological capital) about the future’s expectancy for it would contribute not only for a better operation in the employee’s social and personal life but the possibility of a schedule for a emotional education and functionality in the organization.